Models of the Multinational Enterprise - Buckley, Peter J.; Casson, Mark C. (Journal of International Business Studies, 1998)
Flexibility is identified as the hallmark of recent modelling of the multinational enterprise. The focus on flexibility is a response to the rationalization and restructuring of international business, which has occurred since the end of the “golden age” of Western economic growth. Flexibility has been south in factor markets, intermediate product markets and markets for final products. It has been sought by both governments and firms. Flexible firms are attracted to locations with flexible host governments. This article contrasts the modern research agenda based on flexibility with the more traditional research agenda which predominates in the literature reviewed by Caves (1996).